The Effect of Price and Product Variants on Snack Purchase Decisions with Buying Interest as an Intervening Variable in Students of Gadingmangu Jombang Islamic Boarding School - Siska Ayu Pradipta; Nurul Badriyah; Titin Titin (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the effect of price and product variety on snack purchase decisions with buying interest as an intervening variable among students of Gadingmangu Islamic Boarding School, Jombang. This study employs an associative quantitative approach. The population consisted of 4,120 students, with a sample of 98 respondents selected using the Slovin formula and simple random sampling technique. Data were collected through Likert-scale questionnaires (1–5) and analyzed using Partial Least Square (PLS) with SmartPLS 3.0. The results show that: (1) price does not significantly affect purchase decisions (β=0.086; T=0.964; p=0.336); (2) product variety significantly affects purchase decisions (β=0.242; T=2.266; p=0.045); (3) price significantly affects buying interest (β=0.172; T=2.009; p=0.024); (4) product variety significantly affects buying interest (β=0.241; T=2.319; p=0.021); (5) buying interest significantly affects purchase decisions (β=0.541; T=6.803; p=0.000); (6) price significantly affects purchase decisions through buying interest (β=0.131; T=2.020; p=0.044); (7) product variety significantly affects purchase decisions through buying interest (β=0.130; T=2.358; p=0.019). These findings imply that entrepreneurs in the Islamic boarding school environment should diversify product varieties and stimulate consumer buying interest to enhance purchase decisions.